A religious minority tax in healthcare? Insights from Muslim American physicians - Sohad Murrar; Laila Azam; Aasim I. Padela (SSM: Qualitative Research in Health, 2023)
Physicians from marginalized racial, ethnic, sexual, and gender backgrounds often encounter adversity, ranging from overt discrimination to subtle microaggressions, which impacts their professional careers. Consequently, concerted efforts to promote workforce diversity in healthcare have begun to tackle these issues. In this study, we further these efforts by uplifting the voices of a minority religious community, Muslim physicians, and their experiences in the medical profession. Using a community-engaged research approach, we recruited 18 physicians from 3 national Muslim clinician organizations who had worked at a university hospital within the last 20 years to participate in semi-structured interviews focused on how their religious identity intersects with experiences of discrimination and accommodation. Deploying a phenomenological framework, we identified four emergent themes that cut across the 18 interviews. The physicians’ experiences demonstrated that they i) shouldered extra labor to uphold their religious identity, (ii) denied their personal experiences of religious discrimination, (iii) feared religious discrimination, and (iv) mislabeled their personal management of religious practices as institutional accommodations. These experiences suggest that the additional responsibilities and burdens that saddle underrepresented racial and ethnic identities in medicine – dubbed “the minority tax” – extend to this religious minority group. They also highlight a unique set of psychological and professional costs associated with carrying a Muslim identity in the physician workforce. Our findings underscore the need for healthcare systems to take bold action in creating non-discriminatory, inclusive, and equitable working environments that attend to the religious identities of diverse physicians.